Tejidos que andan (2021)
In the first place, the intention is to start an exploratory and experimental journey within the training as a Master in Fine Arts, to reach the point of an artistic creation, which is a sensitive manifestation of a way of reading and experiencing the notion of weaving more Beyond what as a job and later as a game, gave a lot to think about, and here I reveal myself in a personal way, in a turn of possibilities towards the social fabric, a complex concept, which can also be understood from reflection on daily life and the interpersonal relationships; and of course, complete the academic training as a teacher in Fine Arts in which I give myself as I am.